The effects of tumor‐derived exosomes on T‐cell function and efficacy of cancer immunotherapy. Issue 2 (14th September 2021) - Hao, Yuanyuan; Chen, Panpan; Zhang, Xuzhao; Shao, Yanping; Xu, Yang; Qian, Wenbin
Abstract: Tumor‐derived exosomes (TEXs) are a class of extracellular vesicles which play an important role in the tumor microenvironment. These vesicles have multiple biological functions including promotion of cancer progression and reduction of anti‐tumor immunity. Recently, interaction between TEXs and immune cells are of great interest in cell‐based immunotherapy. Here, we review the effects of TEXs on the survival and functions of T cell subsets, as well as their clinical applications. Unraveling the immunoregulatory function of exosomes allows a better understanding of the molecular and cellular basis for cancer immunotherapy.